Library Satisfaction Level of Library Services at Library of Muhammadiyah University of North Sumatera - Yuniar, Rizkia; Siregar, Yusra Dewi (International Journal of Cultural and Social Science, 2022)
The research objective was to determine the services available and to determine the level of satisfaction of visitors to services at the Muhammadiyah University of North Sumatra Library. This type of research is a quantitative study with an inferential approach. The population in this study were students who were still actively visiting the library of the Muhammadiyah University of North Sumatra, totaling 1,380 people. Samples were taken using the Slovin formula and obtained a sample of 93 people. The method of collecting data with a questionnaire using a Likert scale. Testing research instruments with validity and reliability tests. Data analysis using simple linear regression analysis analysis method. The hypothesis which states the influence of visitor satisfaction on UMSU library services is acceptable. The percentage of satisfaction of visitors to UMSU library services is 77.9%, while 22.1% of visitor satisfaction is influenced by other variables not examined.